Pengaruh Struktur Modal Terhadap Profitabilitas Pada Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Sarah, Desi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
This study aims to determine the effect of Capital Structure on Profitability. The financial ratios used to measure the effect are Debt to Equity Ratio (DER), Debt to Assets Ratio (DAR), Equty to Assets Ratio (EAR) and Return on Equity (ROE). This type of research is associative and the sampling technique used is purposive sampling technique. The sample was 15 Food and Beverage Sector Manufacturing Companies listed on the Indonesia Stock Exchange for the 2019-2023 Period. The data analysis technique used is multiple linear regression analysis. The results of the multiple linear regression analysis are Y = 0.411-2.181X1-1.155X2+1.936X3 and the results of hypothesis testing prove that partially the Debt to Equity Ratio (DER) variable with t table> t count is 1.66660> -9.442 and significance 0.000 <0.05 which indicates there is a negative but significant effect on Return on Equity (ROE), Debt to Assets Ratio (DAR) with t table> t count is 1.66660> -1. 733 and significance 0.088> 0.05 which shows there is a negative but insignificant effect on Return on Equity (ROE) and Equty to Assets Ratio (EAR) with t table < t count, namely 1.66660> 2.380 and significance 0.020 < 0.05 which shows a positive but significant effect on Return on Equity Ratio (ROE). Simultaneously the variables Debt to Equity Ratio (DER), Debt to Assets Ratio (DAR) and Equty to Assets Ratio (EAR) with f table < f count 2.50 < 31.115 and significance 0.000 < 0.05 indicate a significant effect on Return on Equity Ratio (ROE). Keywords: Debt to Equity Ratio (DER), Debt to Assets Ratio (DAR), Equity to Assets Ratio (EAR), and Return on Equity Ratio (ROE)